2019
DOI: 10.1186/s13023-018-0973-5
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expressions of miRNA-206 target, FN1, in multifactorial Hirschsprung disease

Abstract: BackgroundMicroRNAs (miRNAs) have been associated with the Hirschsprung disease (HSCR) pathogenesis, however, the findings are still inconclusive. We aimed to investigate the effect of miRNA-206 and its targets, fibronectin 1 (FN1), serum deprivation response (SDPR), and paired box 3 (PAX3) expressions on multifactorial HSCR in Indonesia, a genetically distinct group within Asia.MethodsWe determined the miRNA-206, FN1, SDPR and PAX3 expressions in both the ganglionic and aganglionic colon of HSCR patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…A recent study suggested that the expression of THBS1 was modulated by multiple miRNAs (67). Moreover, it's reported that fibronectin 1 ( FN1 ) is crucial to many cellular processes, including cell proliferation, adhesion, migration and differentiation (68, 69), and the expression of FN1 was regulated by miR-1271 (70), miR-9 (71), and miR-206 (72). Similar to previous studies, we identified the negatively regulated miRNA-mRNA pairs in the CS-induced lung cancer, which were implicated in several cancer-related (especially EMT-related) biological process and KEGG pathways in the malignant transformation progress of lung cells induced by CS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the expression of THBS1 was modulated by multiple miRNAs (67). Moreover, it's reported that fibronectin 1 ( FN1 ) is crucial to many cellular processes, including cell proliferation, adhesion, migration and differentiation (68, 69), and the expression of FN1 was regulated by miR-1271 (70), miR-9 (71), and miR-206 (72). Similar to previous studies, we identified the negatively regulated miRNA-mRNA pairs in the CS-induced lung cancer, which were implicated in several cancer-related (especially EMT-related) biological process and KEGG pathways in the malignant transformation progress of lung cells induced by CS.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the regulation of FN1-mediated brosis by miRNAs. Gunadi et al [31] reported that miRNA-206 targeting FN1 is abnormally expressed in multifactorial Hirschsprung's disease and can be used as a potential targeting molecule. Moreover, an interesting phenomenon was found in this study: BSMCs undergo apoptosis after miR-219c-5p is overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…A novel anti brotic function of miR-133 was proposed, which represents a potential target for diagnosis and treatment strategies for bladder brosis. Gunadi et al [31] reported that miRNA-206 targeting FN1 is abnormally expressed in multifactorial Hirschsprung's disease and can be used as a potential targeting molecule. Moreover, an interesting phenomenon was found in this study: BSMCs undergo apoptosis after miR-219c-5p is overexpressed.…”
Section: Discussionmentioning
confidence: 99%